ACTR-67. PATTERNS OF CARE AND IMPACT ON SURVIVAL OF FIRST SALVAGE THERAPY IN HIGH-RISK GRADE II GLIOMAS FOLLOWING INITIAL TEMOZOLOMIDE. (11th November 2019) - Pellerino, Alessia; Bello, Lorenzo; Conti Nibali, Marco; Bruno, Francesco; Mo, Francesca; Pronello, Edoardo; Soffietti, Riccardo; Rudà, Roberta
Abstract: BACKGROUND: No standard treatment is validated at first progression in high-risk low-grade gliomas, thus the optimal salvage therapy at recurrence and the factors that influence the PFS and OS are being investigated. MATERIAL AND METHODS: We evaluated 71 patients with grade II glioma (WHO 2016) who progressed following surgery and initial chemotherapy with TMZ. Thirty-two (45.1%) patients were oligodendrogliomas IDH 1/2 mutated and 1p19q codeleted, 11 (15.5%) were diffuse astrocytomas IDH mutant, and 28 (39.4%) were diffuse astrocytomas IDH wild-type. Median follow up was 144 months (range 23–180). RESULTS: Thirty-one patients (43.7%) underwent second surgery, 24 (33.8%) second-line chemotherapy, and 16 (22.5%) radiotherapy with a median PFS of 58 months (IC 95% 49–116). Median PFS was 60 months after second surgery (IC95% 43–116) and chemotherapy (IC95% 51–69), and 38 months after radiotherapy (IC95% 15–64) (p 0.09). No significant benefit in PFS was achieved in oligodendrogliomas undergoing second surgery (60 months) as compared with oligodendrogliomas treated with radiation or chemotherapy (58 months, p 0.11). PFS of astrocytomas IDH wild-type following second surgery (53 months) did not differ from those patients treated with adjuvant treatments (65 months, p 0.28). Median OS from the first salvage therapy was 117 months (IC95% 93 – 123 + ): 120 months (IC95% 108–140 + ) after second surgery, 94 months (IC95% 75–117 + ) after chemotherapy, and 62 months (IC95% 27–112) after radiotherapy (p 0.04). Median OS (123 months, IC95% 106–154) was prolonged in oligodendrogliomas receiving second surgery as compared to those receiving radiotherapy or chemotherapy (93 months, IC 95% 61–112, p 0.07), while median OS in astrocytomas IDH wild-type did not differ between those who received second surgery or radiotherapy or chemotherapy. CONCLUSION: Reoperation as first salvage treatment in grade II gliomas seems to offer a probability of a longer OS, and this could hold true especially for oligodendrogliomas.